Penerapan Layanan Bimbingan Kelompok dalam Mencegah Penurunan Kualitas Moral Peserta Didik - Jumairiansyah, Jumairiansyah; Ferdiansyah, M.; Noverina, Romadona; Arizona, Arizona (Bulletin of Counseling and Psychotherapy, 2020)
Problems that occur in schools are associated with a decrease in the moral quality of students that is behaving rudely, speaking harshly, and telling lies to teachers and peers. The purpose of this study is to determine the effectiveness of the application of group guidance services in preventing decline in moral quality of students. The method used in this research is a quantitative approach with pre experimental methods with one group pretest and posttest design. The sample in this study amounted to 10 students based on the lowest score category 5 students and 5 students were in the highest score category in Class XI Office Administration. Data collection techniques using a questionnaire decreased the quality of morality with a validity test using the coefficient formula Product moment correlation and reliability using the Spearman Brown formula. The results of the study concluded: that the pretest results of decreased moral quality by 100.7 and posttest results by 195.9 so that there was a pretty good improvement after obtaining group guidance services to decrease the moral quality of students. So, the application of group guidance services effectively prevents the decline in moral quality of students in SMK Negeri 1 Pemulutan.